Management Of Religiously Based Higher Educational Institutions In Facing The Society 5.0 Era In Langkat Naval Teacher And Educational School - Nasution, Khairani; Rafida, Tien; Nasution, Sahkholid (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to reveal: 1) How to conceptualize Management Development- Based Higher Education Deeply religious Facing the Era of Society 5.0 at Al Maksum College of Teacher Training and Education Step; 2) How to Implement Management Institution- Based Higher Education Religious in Facing the Era of Society 5.0 in Schools Al Maksum Teacher Training and Education College Step; and 3) What are the Implications Management Higher Education Based Institutions Religious in Facing the Era of Society 5.0 at the Al Maksum Teacher Training and Education College Langkat. The results of this research are: 1) The management concept at STKIP Al Maksum Langkat is based on SN DIKTI, implementing the tri dharma of higher education based on the belief in Almighty God which has the characteristics of character, integrity, innovative, creative, religious and scientific; 2) Implementation management based religion in the era of society 5.0. 3) Implications management at STKIP Al Maksum Langkat.